Evaluation on the effect of butternut pumpkin (Cucurbita moschata) maturity stage on the bioactive components and antioxidant activity of pumpkin flour - Siti Nurdjanah; Nurbaiti Nurbaiti; Sussi Astuti; Tanto Pratondo Utomo; Sartika Dewi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Pumpkin flour is a processed product high in carotenoids and a good source of nutrients. This nutritional content of pumpkin flour was considered to be influenced by the fruit maturity stage. Therefore, this research aimed to evaluate pumpkin flour's chemical properties, bioactive components, and antioxidant activity at different maturity stages. This also used honey pumpkins with a maturity stage of 15, 20,25, and 30 days after fruit set( DAFS). The results showed that the maturity stage of butternut pumpkin affects the moisture content and bioactive components such as phenols, flavonoids, and carotenoids of flour produced. Furthermore, the highest antioxidant activity was found in pumpkin flour with a maturity stage of 25 DAFS with IC50 values of 85.31 Âµg/mL (DPPH) and 64.39 g/mL (ABTS). Therefore, butternut pumpkins with a maturity stage of 25 DAFS can be processed into flour with antioxidant properties.